Pengembangan Ensiklopedia Morfologi, Anatomi dan Fisiologi pada Tumbuhan Berkarakter Khusus - Dede Nuraida; Umi Mahmudatun Nisa (Universitas Sebelas Maret, 2017)
This development research is based on the few biological reference books available in the community. The rapid increase of science leads to increased demand for new books with new material that fits developments and is easy to understand. This research development aims to determine the level of book worthiness and response of the use of encyclopedia books that have been developed. This research is a research development (Research & Development) which use model development of ADDIE. The data collection instrument uses the material expert's validation sheet and the media expert by the education lecturer as a validator to know the feasibility level of books and user response sheets by junior and senior high school students, biology students, biology teachers and lecturers of biology education. Further data obtained were analyzed using Likert scale. From the results of data analysis can be obtained the validation of the material is 4,50 and the results of media expert validation is 3,60 so that the feasibility level of the encyclopedia that has been developed is feasible tested and no need for revision. While the reader response, the score obtained is 4.55 so that the encyclopedia that has been developed declared qualified and acceptable and used in the community.